2013
DOI: 10.1002/jts.21818
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic Stress Symptomatology as a Mediator of the Relationship Between Warzone Exposure and Physical Health Symptoms in Men and Women

Abstract: The mediating role of posttraumatic stress symptomatology (PSS) on the association between warzone exposure and physical health symptoms in 7 bodily systems (cardiovascular, dermatological, gastrointestinal, genitourinary, musculoskeletal, neurological, and pulmonary) was examined. We also examined if mediation effects varied as a function of sex. A sample of 317 U.S. Gulf war veterans was assessed for warzone exposure, PSS, and physical health symptoms 10 years after deployment. PSS was significantly associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 56 publications
3
22
0
Order By: Relevance
“…Some of the findings from the causal mediation analysis are in accordance with the well‐established hypothesis that PTSS may act as a mediator between exposure to trauma and poor physical health (Eadie, Runtz, & Spencer‐Rodgers, ; Green & Kimerling, ; Schnurr & Green, ; Schnurr & Jankowski, ; Wachen et al., ). We believe that there is a lack of research on whether PTSS may act as a mediator linking physical injury specifically to somatic complaints.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Some of the findings from the causal mediation analysis are in accordance with the well‐established hypothesis that PTSS may act as a mediator between exposure to trauma and poor physical health (Eadie, Runtz, & Spencer‐Rodgers, ; Green & Kimerling, ; Schnurr & Green, ; Schnurr & Jankowski, ; Wachen et al., ). We believe that there is a lack of research on whether PTSS may act as a mediator linking physical injury specifically to somatic complaints.…”
Section: Discussionsupporting
confidence: 82%
“…On the other hand, exposure to physical injury has been closely associated with posttraumatic stress symptoms (PTSS) after a range of traumatic events (Bonanno, Galea, Bucciarelli, & Vlahov, 2006;Bugge et al, 2015;Hsu, Chong, Yang, & Yen, 2002;Kuo, Wu, Ma, Chiu, & Chou, 2007;Neria, DiGrande, & Adams, 2011;Perlman et al, 2011). Also, a significant association between PTSS and poorer physical health has been found in several studies, and the mediating role of PTSS between trauma exposure and poorer somatic health was hypothesized early on (Green & Kimerling, 2004;Gupta, 2013;Pacella, Hruska, & Delahanty, 2013;Wachen et al, 2013;Zatzick, Russo, & Katon, 2003;Zatzick et al, 2008). However, research on the relationship between exposure to traumatic events, posttraumatic stress (PTS), and somatic complaints has been limited.…”
Section: Wentzelmentioning
confidence: 99%
See 1 more Smart Citation
“…This mediation is highly plausible because PTSD and other mental disorders have been repeatedly associated with concurrent and subsequent poor physical health [2][6]. Despite this, the role of PTSD remains unclear, because although many studies have found PTSD to mediate associations between traumatic event exposures and physical health [7][14], other studies have suggested that trauma exposure has independent associations with physical health problems [15][22]. This question of whether traumatic stress is associated with increased risk of physical ill-health independently of PTSD has important implications for the mechanisms linking trauma and physical health and for treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of ED in the general population was reported at 4.7% [1], while at 20% to 27% in combat veterans in the military population [4], PTSD was found to be significantly associated with both post-deployment physical and chronic mental health disorders [5]. Patients with PTSD were reported to experience flashbacks related to PTSD incidents, and the U.S. Department of Veterans Affairs reported 11% to 20% of combat veterans of Iraq and Afghanistan may undergo PTSD-related flashbacks for years [6].…”
Section: Discussionmentioning
confidence: 99%